Genetic structure of Mount Huang honey bee (Apis cerana) populations: evidence from microsatellite polymorphism. (December 2016) - Liu, Fang; Shi, Tengfei; Huang, Sisi; Yu, Linsheng; Bi, Shoudong
Abstract Background The Mount Huang eastern honey bees (Apis cerana ) are an endemic population, which is well adapted to the local agricultural and ecological environment. In this study, the genetic structure of seven eastern honey bees (A. cerana ) populations from Mount Huang in China were analyzed by SSR (simple sequence repeat) markers. Results The results revealed that 16 pairs of primers used amplified a total of 143 alleles. The number of alleles per locus ranged from 6 to 13, with a mean value of 8.94 alleles per locus. Observed and expected heterozygosities showed mean values of 0.446 and 0.831 respectively. UPGMA cluster analysis grouped seven eastern honey bees in three groups. Conclusion The results obtained show a high genetic diversity in the honey bee populations studied in Mount Huang, and high differentiation among all the populations, suggesting that scarce exchange of honey bee species happened in Mount Huang. Our study demonstrated that the Mount Huang honey bee populations still have a natural genome worth being protected for conservation.